PENYIAPAN BAHAN KHUSUS EKSTRAK ETANOL DAUN SIRSAK SEBAGAI KOMPONEN PAKAN UNTUK IMMUNOSTIMULAN PADA BUDIDAYA IKAN GURAMI - Nunung Komalawati; Yus Chandrawati; Sulastuti Sulastuti; Siti Anisah (UIN Sunan Kalijaga Yogyakarta, 2018)
Soursop leaf contains various secondary metabolites with several functions such as antioxidant, antibacterial, and immune-stimulant. Supplementation of soursop leaf extract on fish pellet might become immune-stimulant which decreases the mortality of giant gourami seeds. The aims of this study were to obtain ethanol extract of soursop leaf and utilize the extract as immune-stimulant on fish pellet. Leaf extraction was performed using explorative survey, while biological test was done using completely randomized design. Ethanol absolute was used as a solvent during extraction with the ratio between soursop mill and ethanol was 1:10. Pelarut yang digunakan untuk ekstraksi adalah ethanol absolute dengan perbandingan 1:10 (daun sirsak: etanol). Two treatments were done during biological tests, those was pellet with 0.5% of soursop extract supplementation and pellet without extract supplementation. The treatments were repeated for five times. Giant gourami seeds from both treatments were infected by 0.2 mL of A. hydrophila with cell concentration of 10-8 CFU. The seeds were reared and their survival and mortality were counted. The result of the extraction was analyzed descriptively, whereas survival and mortality were analyzed using t-test. The extraction of 700 g soursop mill results in 125 g of extracts. The gourami seeds fed by commercial pellet with extract supplementation had 96% survival and 4% mortality. Nevertheless, gourami seeds fed by commercial pellet without extract supplementation was only has 8% survival and 92% mortality. The t-test proved that soursop extract supplementation on commercial pellet was able to increase fish survival and decrease the mortality. Therefore, ethanol extract of soursop leaf can be used as immune-stimulant on giant gourami seeds.